Improving the rhythm perception of teenage footballers - Sablin, A.B.; Kornishin, I.I.; Chernyshev, S.V.; Strelnikova, I.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to improve the rhythmic abilities of 15-16-year-old adolescents through football techniques and exercises. Methods and structure of the study. 46 athletes from a sports school in Moscow took part in the pedagogical experiment. Children from the control group followed the standard programme, while children from the experimental group performed special exercises to develop their sense of rhythm for 15 minutes during each training session. Rhythm ability was assessed using the ‘Pull the ball with the foot’ test, as well as the ‘Snake’ test, which assesses the overall technical preparedness of footballers. Results and conclusions. Before the start of the study, there were no significant differences (p>0.05). After the educational experiment, the results in the control group in the ‘Pull the ball with the foot’ test improved from 6.1±0.2 to 5.7±0.1 (p>0.01), and in the ‘Snake’ test from 9.8±0.6 to 9.1±0.5 (p>0.01). These results indicate the low effectiveness of the standard programme for developing technical skills and a sense of rhythm in 15-16-year-old footballers. The experimental group’s results in the ‘Pull the ball with the foot’ test improved from 6.2±0.3 to 5.1±0.1 (p<0.01), and in the ‘Snake’ test, the results improved from 9.7±0.5 to 8.2±0.4 (p<0.01), which indicates the effectiveness of introducing special exercises to improve rhythm in the training process for footballers. The systematic use of means and methods for developing agility, in particular rhythm ability, in football training sessions with athletes aged 15-16 has a visible positive effect on the technical preparedness of football players and significantly improves their sense of rhythm.